P250 Transcranial direct current stimulation of the prefrontal cortex disrupts learning in a working memory task. Issue 3 (March 2017) - Nikolin, S.; Boonstra, T.; Martin, D.; Loo, C.
Abstract : Introduction: Transcranial direct current stimulation (tDCS) of the prefrontal cortex in healthy participants has been shown to improve working memory (WM) performance. Electrophysiological recordings (EEG) during a WM task have demonstrated changes in the lower frequencies of neuronal electrical activity following anodal stimulation of the left dorsolateral prefrontal cortex (DLPFC). However, results are highly heterogeneous and the interaction between tDCS, neural oscillations, and performance outcomes is not yet well understood. Previous EEG studies in healthy participants have shown that the peak of an individual's alpha frequency (IAF) is associated with WM performance. Objective: We therefore aimed to investigate the effects of anodal tDCS to the left DLPFC on WM performance while monitoring oscillatory brain activity, including IAF, using EEG. Method: Forty healthy participants received 15 min of active or sham tDCS in a single-blind, parallel group, placebo-controlled trial. Anodal stimulation was applied to the left DLPFC for 15mins at 2 mA with the cathode placed over the right DLPFC. Participants completed a WM (3-back) task, and EEG eyes-open resting state data was obtained, prior to, during, and following tDCS. Results: Results showed that active tDCS did not improve discriminative sensitivity on the 3-back task over time (raw change d ′ = 0.13, 95% CI [−0.17 to 0.43], p  = 0.39), while in the sham condition participants showed increased performance (raw change d ′ = 0.52, 95% CI [0.17–0.88], p  = 0.01). IAF peaks recorded over occipital brain regions significantly increased from pre- to post-tDCS in both groups. IAF changes were strongly correlated with performance improvement from pre- to post-tDCS in the sham condition ( r  = 0.592, p  = 0.01), but not in the active tDCS condition ( r  = 0.188, p  = 0.50). Conclusion: These results confirm that tDCS applied to the left DLPFC can modulate WM performance. However, contrary to expectations, WM performance improved with sham but not active tDCS, suggesting active tDCS impaired learning. Additionally, tDCS seemed to disrupt the relationship between individual IAF and WM outcomes. This highlights the need to investigate the dose–response relationship for tDCS and to individualise tDCS settings to achieve optimal outcomes.